2013
DOI: 10.4319/lo.2013.58.5.1605
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic identification, seasonal dynamics, and potential transmission mechanisms of a Daphnia‐associated single‐stranded DNA virus in two temperate lakes

Abstract: We used a metagenomic approach to identify viruses that may be involved in the ecology of Daphnia spp. in Oneida and Cayuga lakes (upstate New York). We identified several highly represented, putative eukaryotic, circular, single-stranded deoxyribonucleic acid (DNA) viral genomes. Among these, we discovered a genotype similar in both sequence and genomic architecture to a virus previously reported from a hyperthermal lake that shares characteristics of both single-stranded ribonucleic acid (RNA) and single-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 67 publications
2
33
0
Order By: Relevance
“…Note added in proof: Following the revision of this article, Hewson et al have described the identification of a new CHIV genome in samples collected from Oneida and Cayuga lakes (upstate New York, USA) 71 , further expanding our knowledge on the genetic diversity and environmental distribution of this peculiar group of chimeric viruses. Interestingly, the new ssDNA virus appears to be associated with planktonic crustaceans of the genus Daphnia.…”
Section: Discussionmentioning
confidence: 99%
“…Note added in proof: Following the revision of this article, Hewson et al have described the identification of a new CHIV genome in samples collected from Oneida and Cayuga lakes (upstate New York, USA) 71 , further expanding our knowledge on the genetic diversity and environmental distribution of this peculiar group of chimeric viruses. Interestingly, the new ssDNA virus appears to be associated with planktonic crustaceans of the genus Daphnia.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these viruses have been identified in insects [2,5,16,17], copepods [6], mollusks [4] and water fleas [8]. Although recent studies have identified linear ssDNA densoviruses in echinoderms [7,9], AfaCV is the first CRESS-DNA virus identified in echinoderms and provides further support that these viruses may infect a wider host range than previously thought.…”
mentioning
confidence: 95%
“…Quantitative PCR (qPCR) was performed following the approach of Hewson et al (17), where template material comprised DNA extracted from small excisions of body wall or tube feet and where SSaDV copy number was divided by weight of tissue extracted.…”
Section: Investigation Of Viral Agents In Sswd-affected Tissuesmentioning
confidence: 99%